Enhancing Scientific Literacy and Numeracy Using Ethnobiology E-Modules Integrated with AK-Based Multimodal Learning Activities - Lesy Luzyawati; Idah Hamidah; Husamah; Putri Slamet; Ahmad Adnan Mohd Shukri (Jurnal Inovasi Pendidikan IPA, 2026)
Indonesia's scientific literacy and numeracy skills remain relatively low compared to those of other countries. This deficiency is often linked to factors such as inappropriate textbooks, non-contextual learning, and low reading proficiency. This study aimed to determine the effect of an interactive, ethnobiology-based e-module, integrated with Visual, Auditory, and Kinesthetic (VAK)-based multimodal learning activities, on students' numeracy and scientific literacy skills in biodiversity material, considering different learning styles. This study employed a quantitative approach using a posttest-only quasi-experimental design with a 2 × 3 factorial structure. The population comprised all tenth-grade students at SMA Negeri 1 Indramayu. Two classes, X-4 (experimental) and X-3 (control), were selected through cluster random sampling at the class level, with a total of 87 students (43 in the experimental class and 44 in the control class). The experimental class learned through an interactive ethnobiology-based e-module accompanied by multimodal visual, auditory, and kinesthetic activities. Meanwhile, the control class learned through the school’s conventional instruction using PowerPoint, textbook-based explanation, teacher-led discussion, and instructional videos. Data analysis was conducted using a two-way ANOVA test on the composite posttest score. The results indicated a highly significant difference in students’ posttest achievement between the experimental group and the control group (sig. 0.000<0.05). Conversely, learning style alone did not show a significant difference (sig. 0.303>0.05). Furthermore, the analysis revealed no significant interaction between the use of the e-module and students' learning styles (sig. 0.510>0.05). These findings indicate that, within this research context, the ethnobiology-based interactive e-module effectively supported higher students' numeracy and scientific literacy skills, irrespective of their individual learning styles. The study contributes empirical evidence that contextualized digital teaching materials support science learning while also showing that multimodal instruction may be more influential than learning-style categorization itself.